Unpaid Care Work in the Republic of Belarus: Structure Analysis and Methods of Macroeconomic Assessment - N. V. Agabekova; A. V. Korolenok (Статистика України, 2019)
Achieving gender equality is important for sustainable socio-economic development of the country. The significance of this problem is also reflected in the Sustainable Development Goals, namely, achieve gender equality (Goal 5). While the Republic of Belarus pays great attention to solving gender problems, inequality in the labor market is persisting. In particular, gender differences in the distribution of paid and care-related work still exist. Therefore, it is important to study and identify the differences in the time budget of employed men and women in the Republic of Belarus, with assessing the unpaid household services and their recording in national accounts.